Studies on the variability of upwelling system in the South Central Vietnam waters under the impact of ENSO events and its impact on hydrographic conditions of the Ninh Thuan-Binh Thuan waters - Chung, Tran Van; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2019)
In this paper, we have exploited and analyzed data from HYCOM + NCODA Global 1/12.5o Reanalysis database in the period of 20 years from 1993 to 2012 and from 2013–8/2016 for the data assimilation of the HYCOM + NCODA Global 1/12° Reanalysis - for 22 depth layers in the East Sea area. The research results show that there are changes in the upwelling phenomenon and hydrological structure in the Ninh Thuan - Binh Thuan waters under the influence of ENSO phenomenon as follows: La Niña can degrade and eliminate the upwelling phenomenon. In the waters of Ninh Thuan - Binh Thuan when upwelling phenomenon occurs, it often manifests itself in the rapid decline of seawater temperature and rapid increase in seawater salinity in the depth layer of 50–100 m. The research results also show that in the East Sea region in 2010, during the Southwest monsoon season (July 2010), the phenomenon of downwelling occurred quite strongly in the middle of the Hoang Sa archipelago and the west of the Philippines and expanded toward southeast part of Hainan island. The cause of this special dynamic phenomenon may be due to the influence of the wind regime (average wind stress in July 2010)